THE IDENTIFICATION OF ACCOUNTING MANIPULATION IN FINANCIAL STATEMENTS USING BENEISH MODEL (LISTED MANUFACTURING COMPANIES IN IDX DURING 2013-2014) - admin, Willya Putri Suryadi B42112016 (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2016)
The purpose of this study is to identify the suspected manufacturing sector listed in the Indonesia Stock Exchange (IDX) during 2013-2014 which had engaged in the accounting manipulation. The Beneish model was used as a tool to conduct the analysis and assist in evaluating the probability of accounting manipulation in financial statements. The Beneish model is a financial forensic tool which consists of eight variables of ratio index and benchmarks to identify the occurrence of financial fraud or tendency to engage in the accounting manipulation. The eight variables were weighted together according to the Beneish model formula to get the M-Score for every single manufacturing company. The results of M-Score of each company, was then compared with the benchmark set by Beneish (1999), which is -2.22. Based on this approach, the M-Score’s result that is greater than -2.22 indicates that the company has a strong likelihood of an accounting manipulation. The results of this study figured out that about 52 companies or 98% of the total manufacturing companies analyzed as samples which had engaged an accounting manipulation or a strong likelihood of manipulating their financial statements. Only one company or 2% out of the total samples whose its financial statements were free from accounting manipulation practice. Keywords: financial statements, accounting manipulation, Beneish model, manufacturing companies